Histopathological Examination of CT-Guided Lung Biopsy in Patients Attending Tertiary Care Hospital, Nepal: A Cross-Sectional Study - Sinha, Amrita; Sedhain, Sapana; Bhattarai, Soorya (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Among various lesions encountered in the lung, lung cancer is one of the most common cancers and a cause of cancer-related deaths. Among malignancies, non-small cell lung carcinoma is the most common lung cancer. A CT-guided lung biopsy is a quick, reliable, and simple technique with fewer complications than other methods for diagnosing pulmonary lesions. The main objective of this study was to evaluate the histopathological outcomes of CT- guided lung biopsies and to classify the identified lung lesions. Methods: This was a hospital-based, prospective, cross-sectional study conducted from 1st August 2023 to 31st January 2024, with ethical clearance from the Institutional Review Committee (IRC-PA-314/2023). A Convenience sampling included 73 patients. The obtained data were analyzed using Microsoft Excel and Statistical Package of the Social Sciences version 16. Results: The majority of cases with lung lesions were seen in the 71-80 years age group with male predominance. Of the 73 cases included in the study, neoplastic lesions comprised 56 (76.71%), followed by non-neoplastic lesions in 9 (12.33%), and inadequate biopsies in 8 (10.96%). Of the total 56 malignant lesions, the most common histological type was Non-Small Cell Lung Carcinoma, comprising 46 (82.14%), among which adenocarcinoma accounted for 30 (53.57%), followed by Squamous Cell Carcinoma accounting for 16 (28.57%). Conclusions: Lung tumors are quite common in patients presenting with a mass lesion. The most common histological type in this study was Adenocarcinoma.